Effectiveness of Integrated Management of Neonatal Childhood Illness (IMNCI) Tool in Chest X-Ray Positive Pneumonia Cases among Children Ages 2 Months to 5 Years A Cross-Sectional Study - Anwar-Ul-Haque, Jalal Uddin Akbar, Syed Zafar Mehdi, Arshad Hamid Khan, Ashifa Yaqoob, Hamid Mumtaz Durrani, Saif Ul Haque, Anjum Un Noor (Pakistan Journal of Medical & Health Sciences, 2023)
IMNCI tool has widely been applied in many countries for screening, clinical diagnosis, and as a management tool for many common diseases, including cases of pneumonia. This study determines the effectiveness of IMNCI tools in the diagnosis of pneumonia as that of diagnosing pneumonia by gold standard method of X-ray Chest PA view besides finding out the sustainability in using the IMNCI guided antibiotics in managing cases of pneumonia from first care to the tertiary care facilities. Methodology: We conducted a prospective, cross-sectional study among children with World Health Organization (WHO) Integrated Management of Childhood Illness (IMCI) chest-indrawing pneumonia at a tertiary care hospital in Pakistan and assessed CXR examinations. The primary endpoint was interrater reliability between CXR for pneumonia diagnosis among children with WHO IMCI chest-indrawing pneumonia. Results: The study was done among 165 children aged between 2 months to 59 months who have visited Fatima Hospital, Baqai Medical University, due to their medical condition of cough OR fast breathing. Most of the mothers had been taking antibiotics for their sick children before they reached our set up and very few of them (15%) were found adherent to taking IMCI guided IMCI-guided antibiotic Amoxicillin, whereas the rest of all a huge majority of the cases were found using non-IMCI guided antibiotics constituting 85%, means other than oral Amoxicillin. A Sensitivity of 68.75% and a Specificity of 92.3% were found to IMCI tools validity in diagnosing pneumonia against X-ray chest positivity. Conclusion: This study concludes that the accuracy of IMCI tools in recognizing childhood pneumonia was good rather than the diagnosis as that to the positive findings in Xray Chest findings. However, with good sensitivity and the best specificity with high PPV, it can be the best screening tool for the early detection of pneumonia among children<5 years and can achieve a better outcome with in-time recognition, appropriate care seeking, and early intervention avoiding irrational antibiotics. Keywords: ARI: Acute Respiratory Infection, AIDS: Acquired Immunodeficiency Syndrome, BMU: Baqai Medical University, IMCI: Integrated Management of Childhood Illness, IMNCI: Integrated Management of Neonatal & Childhood Illness, WHO: World Health Organization, UNICEF: United Nations International Children’s Education Funds, MDG: Millennium Development Goal, SDG: Sustainable Development Goal, MNCH: Maternal, Neonatal & Child Health Program.